Karen Fjelstad and Nguyê?n Thi? Hiê?n, Spirits Without Borders: Vietnamese Spirit Mediums in a Transnational Age - Coward, Matt (Pomegranate, 2018)
Karen Fjelstad and Nguyê?n Thi? Hiê?n, Spirits Without Borders: Vietnamese Spirit Mediums in a Transnational Age (New York: Palgrave Macmillan, 2011), x + 219 pp., $139.99 (hardcover), $49.99 (paperback), $39.99 (ebook).